Advantages Of The English Test Towardjob Opportunities - Imran Hardi; Patahuddin; Ika Yanti Ziska (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2020)
This research aims to find out the benefits provided for the ownership of English test certificate (TKBI) for job seekers and employees in a job. The need for English test that is used at the level of education as a condition to complete the study is now starting to penetrate into recruitment requirements in the world of work. Therefore, the policy of English test becomes a condition of recruitment of workers in various agencies is currently the main topic.This study uses a qualitative case study research method with the design of participants from job seekers and employees as research objects. The object studied consisted of 5 people consisting of 2 job seekers and 3 employees from different agencies and for data collection sourced from observations, interviews, and documentation. The results of the study showed that the participants supported the many benefits obtained from the ownership of English test certificates, especially to support their careers in the world of work. But on the other hand, this study also found the conclusion that the policy to make the English test a condition of recruitment in various agencies is still not appropriate to apply and the application of the test must adjust to the needs of the relevant agencies.